ANALISIS KORELASI PENGEMBANGAN PRODUK TERHADAP VOLUME PENJUALAN DENGAN PANDEMI COVID SEBAGAI VARIABEL KONTROL PADA UD BESKY JAYA BAKERY - Rafikhein Novia Ayuanti; Trisnia Widuri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Product development is a marketing strategy and a solution to increase sales volume because consumers have more choices to fulfill their desires. There is a possibility that if the company ignores product development, consumers will switch to competing products, if this happens, the company will lose customers or consumers and result in decreased sales volume. But if the product development is carried out in accordance with the wishes, needs and tastes of consumers, it is expected to increase the company's sales volume. Given the increasing level of competition, the company must improve the company's performance, including the variety of products offered, to build long-term relationships with its customers or v vother potential customers. Product is one element of the marketing mix that is very strategic in increasing sales volume.The purpose of this study is to determine whether product development can increase sales volume and to determine the Covid pandemic as a control variable between product development and sales volume.The degree of correlation between product development and sales volume indicates a close relationship between these two variables. With a significance level of 0.00, it means that between product development and sales volume has a significant relationship. Before the pandemic was included as a control variable, product development had a very weak relationship with sales volume. with a significance level of 0.570, which means that the product development variable does not have a significant relationship with sales volume. After the pandemic was included as a control variable, the relationship between product development and sales volume became very close. So it can be concluded that the pandemic acts as a control variable between product development and sales volume.